ANALISIS PERWILAYAHAN KOMODITAS KOPI ROBUSTA DI KABUPATEN CIAMIS - Saepul Aziz; Agus Yuniawan Isyanto; Sudrajat Sudrajat; Muhamad Nurdin Yusuf; Anisa Puspitasari (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The mapping of the potential areas for Robusta coffee in Ciamis regency is done as an effort to develop superior commodities in the plantation sector. This study aims to identify the area of Robusta coffee production base and its distribution characteristics in Ciamis regency. The data used is secondary data in the form of time series data starting from 2017-2019. The analysis used is the Location Quotient (LQ) analysis, locality analysis and specialization analysis. Based on the results of calculations using the robusta coffee production indicator, it can be seen that the base area for the Robusta coffee commodity in Ciamis district is in 13 out of 26 sub-districts. Robusta coffee farming activities are not localized in an area but spread across several districts and do not specialize in robusta coffee farming.